Forecasting of Rubber Export Values in West Kalimantan Using the ARIMA Method - Hesty Pratiwi; Sy. Farini Nurhaliza; Siti Aprizkiyandari (Badan Pusat Statistik Provinsi Kalimantan Barat, 2023)
Rubber is one of the largest commodities in Indonesia after palm oil. Rubber has become the primary export commodity in West Kalimantan. In 2023, the export value of rubber in West Kalimantan experienced fluctuations every month. These changes can have a negative impact on the economy in West Kalimantan. Forecasting the value of rubber exports is crucial because the data on rubber export values is often used as a basis for economic planning in a region. The objective of this research is to determine a suitable model for forecasting the value of rubber exports in West Kalimantan and to forecast the value of rubber exports in West Kalimantan for the next 12 periods using the Autoregressive Integrated Moving Average (ARIMA) method.In the stage of determining the best model, it was found that the best model for forecasting the value of rubber exports in West Kalimantan is the ARIMA (1,1,0) model, with a MAPE (Mean Absolute Percentage Error) value of 20.7%. This means that the forecasting results fall into the acceptable category. The forecasting results can be used as an early warning for policy-making related to rubber exports in the upcoming periods.